outcome of Baghdad culture medium and in vitro fertilization of human eggs and embryo transfer outcome - AL- barzanchi, mundhir T.; Al-Anssari, Saeeda A.M.; Balafair, Amer S.; Khunda, Sarmad S. (Journal of the Faculty of Medicine Baghdad, 2006)
Background: